11th GCC Closed Forum: cumulative stability; matrix stability; immunogenicity assays; laboratory manuals; biosimilars; chiral methods; hybrid LBA/LCMS assays; fit-for-purpose validation; China Food and Drug Administration bioanalytical method validation. (20th April 2018) - Islam, Rafiq; Briscoe, Chad; Bower, Joseph; Cape, Stephanie; Arnold, Mark; Hayes, Roger; Warren, Mark; Karnik, Shane; Stouffer, Bruce; Xiao, Yi Qun; van der Strate, Barry; Sikkema, Daniel; et al.
The 11th Global CRO Council Closed Forum was held in Universal City, CA, USA on 3 April 2017. Representatives from international CRO members offering bioanalytical services were in attendance in order to discuss scientific and regulatory issues specific to bioanalysis. The second CRO–Pharma Scientific Interchange Meeting was held on 7 April 2017, which included Pharma representatives' sharing perspectives on the topics discussed earlier in the week with the CRO members. The issues discussed at the meetings included cumulative stability evaluations, matrix stability evaluations, the 2016 US FDA Immunogenicity Guidance and recent and unexpected FDA Form 483s on immunogenicity assays, the bioanalytical laboratory's role in writing PK sample collection instructions, biosimilars, CRO perspectives on the use of chiral versus achiral methods, hybrid LBA/LCMS assays, applications of fit-for-purpose validation and, at the Global CRO Council Closed Forum only, the status and trend of current regulated bioanalytical practice in China under CFDA's new BMV policy. Conclusions from discussions of these topics at both meetings are included in this report.